Design and implementation of 75~110 GHz elliptical dual balun in 90 nm CMOS for W-Band transceiver. Issue 2 (1st February 2019) - Lin, Yo-Sheng; Lin, Yun-Wen
ABSTRACT: We demonstrate an elliptical dual balun structure for 94 GHz image radar transceiver. The results of two prototypes with small chip size of 0.0256 mm 2 are reported. For the first one (i.e. dual balun 1), the input couple-line width is 4 mm and coupled-line space is 2 µm. That is, the distance between the output couple-lines is 8 mm. For the second one (i.e. dual balun 2), the input couple-line width is 2 mm and coupled-line space is 3 mm. The distance between output couple-lines is also 8 mm. The other geometric parameters of the two dual baluns are the same. In a star double-balanced mixer or a four-way power amplifier, the dual balun is applicable for four-way power splitting. Over the 92 ~ 96 GHz, dual balun 1 attains prominent S11 of −14.4~ −16.4 dB, S21 of −7.61~ −7.67 dB, S31 of −8.78~ −8.93 dB, S41 of −7.43~ −7.6 dB, S51 of −9.68~ −9.89 dB, amplitude imbalance magnitude (AIM) smaller than 2.39 dB, and phase difference deviation (PDD) smaller than 3.6°. Furthermore, dual balun 2 attains remarkable S11 of −13.8~ −14.8 dB, S21 of −7.8~ −7.95 dB, S31 of −8~ −8.39 dB, S41 of −7.46~ −7.72 dB, S51 of −8.18~ −8.54 dB, AIM smaller than 0.95 dB, and PDD smaller than 3.8°, close to those of dual balun 1.